ICT as generators of social exclusion in university educational practices - Martha Patricia Astudillo Torres; Florlenis Chevez Ponce; José Alonso Figueroa Gallegos (Universidad de La Rioja, 2021)
This article presents the results of an investigation that analyzes the integration of Information and Communication Technologies (ICT) in university educational processes and the generation of social exclusion that is carried out from the technological incorporation in the education of professionals in civil engineering. The study is contextualized in a Mexican higher education institution and is positioned from the Positivist paradigm through an unpublished scale based on the assumptions of the Classical Test Theory. The main results indicate that the students of the study career have a high perception of social exclusion in this context, that it's associated with the use of ICT, as evidenced by the factorial study that establishes the unidimensionality in the scale and the value of. 768 of Cronbach's alpha, which indicates the existence of a moderate high correlation in the scale used.